Leukocyte counts in different populations of Antarctic Pygoscelid penguins along the Antarctic Peninsula - D'amico, Veronica Laura; Bertellotti, Nestor Marcelo; Benzal, Jesús; Coria, Néstor; Vidal, Virginia; Diaz, Julia Inés; Barbosa, Andrés (Polar Biology)
The Antarctic Peninsula is one of the areas where the climate is changing at the fastest pace, having several effects on the populations of pygoscelid penguins. Few studies have analysed the variation in immune parameters of Antarctic birds in a geographical context; thus, analyses of geographical differences in the immune components of wild pygoscelid penguins are still scarce. Leukocyte counts in birds provide information on their immunity and physiological stress. The objective of this study was to analyse the leukocyte counts in penguins of the genus Pygoscelis (gentoo, Adélie and chinstrap penguins), covering sites along the South Shetland Islands and some islands on the west coast of the Antarctic Peninsula. Our results revealed differences in the number of heterophils and eosinophils and in the heterophil/lymphocyte ratio in the northeastern populations of gentoo and Ade´lie penguins as compared to the rest of the colonies studied. The results contribute to better understanding of the variations in physiological parameters of penguins related to a geographical context. Fil: D'amico, Veronica Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Bertellotti, Nestor Marcelo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Benzal, Jesús. Consejo Superior de Investigaciones Cientificas. Estacion Experimental de Zonas Aridas; España Fil: Coria, Néstor. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Vidal, Virginia. Universidad de Murcia; España Fil: Diaz, Julia Inés. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico la Plata. Centro de Estudios Parasitológicos y de Vectores (i); Argentina Fil: Barbosa, Andrés. Consejo Superior de Investigaciones Cientificas. Museo Nacional de Ciencias Naturales; España